Semi-analytical solution to arbitrarily shaped beam scattering. (July 2017) - Wang, Wenjie; Zhang, Huayong; Sun, Yufa
Abstract: Based on the field expansions in terms of appropriate spherical vector wave functions and the method of moments scheme, an exact semi-analytical solution to the scattering of an arbitrarily shaped beam is given. For incidence of a Gaussian beam, zero-order Bessel beam and Hertzian electric dipole radiation, numerical results of the normalized differential scattering cross section are presented to a spheroid and a circular cylinder of finite length, and the scattering properties are analyzed concisely. Highlights: An exact semi-analytical solution is presented in a spherical coordinate system. This solution is applicable to an arbitrarily shaped beam and object. Numerical results for three shaped beams are provided as examples.